2000
DOI: 10.1111/j.1745-3984.2000.tb01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Limiting Answer Review and Change on Computerized Adaptive Vocabulary Tests: Psychometric and Attitudinal Results

Abstract: Previous simulation studies of computerized adaptive tests (CATs) have revealed that the validity and precision of proficiency estimates can be maintained when review opportunities are limited to items within successive blocks. Our purpose in this study was to evaluate the effectiveness of CATs with such restricted review options in a live testing setting. Vocabulary CATs were compared under four conditions: (a) no item review allowed, (b) review allowed only within successive 5‐item blocks, (c) review allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 10 publications
2
45
0
5
Order By: Relevance
“…Similarly, the possibility of navigating within a test or booklet may interfere with individual test-taking strategies. In particular, the mode effect of a review option has been found to be mediated by student level covariates (e.g., test anxiety, Vispoel 2000) and also to be moderated by test takers' competence (e.g., Vispoel et al 2000).…”
Section: Moderation and Mediation Of Mode Effectsmentioning
confidence: 98%
“…Similarly, the possibility of navigating within a test or booklet may interfere with individual test-taking strategies. In particular, the mode effect of a review option has been found to be mediated by student level covariates (e.g., test anxiety, Vispoel 2000) and also to be moderated by test takers' competence (e.g., Vispoel et al 2000).…”
Section: Moderation and Mediation Of Mode Effectsmentioning
confidence: 98%
“…See Wainer (1993), Wise (1996), and Kingsbury (1996) for discussion of this and other possible score inflation strategies.) Thus, because items are chosen based on previous responses, answer changes on item‐level CATs are not permitted, despite examinees' strong desire for this opportunity (Vispoel, 1998; Vispoel, Hendrickson, & Bleiler, 2000).…”
Section: Item‐level Adaptive Testsmentioning
confidence: 99%
“…A multistage test with linearly administered stages that are adaptively chosen allows examinees to preview and review items within a stage and to change their answers. Because adaptation only takes place between stages, item review and change within stages does not present difficulty for the administration algorithm or vulnerability to response strategies that allow examinees to maximize their scores (Vispoel et al, 2000).…”
Section: Multistage Adaptive Testsmentioning
confidence: 99%
“…Adaptív tesztek bevezetése során számos esetben végezték el az adaptív és a lineáris változat összehasonlító hatékonyságvizsgálatát (Al-A'Ali, 2007;Brossman és Guille, 2014;Frey, Seitz és Kröhne, 2011;Guille, Becker, Zhu, Zhang, Song és Sun, 2011;Hambleton és Xing, 2006;Jodoin, Zenisky és Hambleton, 2006;Kingsbury és Hauser, 2004;Olea, Revuelta, Ximénez és Abad, 2000;Pyper és Lilley, 2010;Rotou, Patsula, Manfred és Rizavi, 2003;Thompson és Way, 2007;Vispoel, Hendrickson és Bleiler, 2000;Zheng, 2012), az eddigi kutatások azonban főként szimulált adatbázisokkal dolgoztak. Empirikus kutatások elsősorban az egyetemista korosztály körében folytak, melyek a legtöbb esetben kis mintán végzett pilotvizsgálatok voltak.…”
Section: I8 Számítógépes Adaptív Tesztek éS Lineáris Tesztek Működéséreunclassified
“…Mivel adaptivitás csak a modulok között valósul meg, így ez nem veszélyezteti a teszt algoritmusát és segíti a tanulókat a minél magasabb pontszám elérésében (Vispoel, Hendrickson és Bleiler, 2000). Az itemalapú adaptív tesztekhez képest jóval kevesebb adminisztrációt és számítógépes számításokat igényelnek (Hendrickson, 2007;Zheng, 2012).…”
Section: I73 a Többszakaszos Tesztek Előnyei éS Hátrányaiunclassified